Epidemiological profile of mortality from esophageal neoplasia in Brazil, Northeast and Sergipe from 2014 to 2019 (Research, Society and Development, 2022)
The objective was to analyze the mortality rates from esophageal neoplasms in Brazil, in the Northeast region and in the state of Sergipe, during the period from 2014 to 2019, from the database available in the Mortality Information System (SIM) of the Department of Informatics of the Unified Health System (DATASUS). Data were arranged as absolute and relative frequency, mean, standard deviation (SD), minimum and maximum. The mortality rate was calculated by dividing the number of deaths from esophageal cancer in a location or period divided by the population of that same location, multiplied by one hundred thousand. The general annual average of deaths from esophageal cancer in Brazil was 4.05 per 100,000 inhabitants. For females, it was 1.77/100,000 women and for males, 6.39/100,000 men. In the Northeast, the overall average was 3.04/100,000 inhabitants, 0.15/100,000 for women and 4.64/100,000 men for men. In the state of Sergipe, the general average was 2.44 deaths/100 thousand inhabitants, followed by 0.97 and 3.99/100 thousand women and men, respectively. For both sexes, there is an increase in death rates from esophageal cancer from 40-49 years of age, with an exponential increase from 50 years of age. There was also a higher mortality from this condition in males both in Brazil, in the Northeast region and in the state of Sergipe.